Scheduling cleaning in a crude oil preheat train subject to fouling: Incorporating desalter control - Ishiyama, E.M.; Heins, A.V.; Paterson, W.R.; Spinelli, L.; Wilson, D.I. (Applied thermal engineering, 2010)
Fouling is a serious operating problem in oil refinery distillation preheat trains (PHTs) as the reduction in heat transfer effectiveness not only reduces the overall rate of heat transfer but also causes difficulty in maintaining key temperatures in the network within their defined operating envelopes. This work considers the problem of controlling the desalter inlet temperature by using hot stream bypassing, within a PHT fouling mitigation strategy based on heat exchanger cleaning. The formulation of the problem is incorporated in the PHT simulator described by Ishiyama et al. (2009) [1]. The methodology is illustrated using a case study based on an industrial network subject to fouling, where the fouling rates of heat exchangers were extracted through a data reconciliation exercise. The case study scenarios suggest that our simulation-based tool should be effective in controlling desalter inlet temperature within a fouling management strategy.